Rate equation analysis of frequency chirp in optically injection-locked quantum cascade lasers - Wang, C; Grillot, F; Kovanis, VI; Bodyfelt, JD; Even, J (Society of Photo-optical Instrumentation Engineers, 2014)
The frequency chirp characteristics of an optically injection-locked quantum cascade laser are theoretically investigated. The key parameter chirp-to-power ratio (CPR) is analytically derived from a full rate equation model. The CPR value can be efficiently reduced by increasing optical injection strength, especially at modulation frequencies less than 10 GHz. In contrast to interband lasers, both positive and negative frequency detuning increase the CPR. Since the frequency detuning is also predicted to enhance the intensity modulation response, a trade-off is required in the optical injection to simultaneously obtain a large modulation bandwidth and low frequency chirp.
Keywords: quantum cascade laser; injection locking; frequency chirp